Overview of ribosomal and non-ribosomal antimicrobial peptides produced by Gram positive bacteria - Tajbakhsh, M.; Karimi, A.; Fallah, F.; Akhavan, M. M. (Cellular and Molecular Biology, 2017)
The increasing incidence of antimicrobial resistance bacterial infection and decreasing effectiveness of conventional antibiotics to treatment have caused serious problems worldwide. The demand for new generationantibiotics to combat microbial pathogens is imperative. Cationic antimicrobial peptides (AMPs) with different sources from prokaryotic to complex eukaryotic organisms, with variable length, amino acid composition and secondary structure, have been consideredduring the past decades. The advantages of large number of AMPs are related to broad spectrum and morphogenetic activities, low resistance rate among microorganismswithout side effect on human cells, rapid killing of bacteria via membrane damage and intracellular targets,and their critical roles in anti-inï¬‚ammatory. Ribosomal synthesized peptides of Gram positive bacteria with various post translational modificationsrepresent extended types of antimicrobial peptide with different structural and functional diversity. These types of peptides have been considered as new therapeutic agents for pharmaceutical development .In addition, non- ribosomal synthesized peptides are a wide range of peptides , an extremely extensive range of biological activities and pharmacological properties that are not synthesized by ribosomes, show interesting biological properties ranging from antibiotic to bio surfactants. This review focused on genetics, mechanism of action and modifications, resistance mode of Gram positive bacteria to AMPs and the biotechnological application of ribosomally and non-ribosomally synthesized peptides derived from Gram positive bacteria.